Recent Developments in Iterative Methods for Reducing Synchronization - Zou, Qinmeng; Magoules, Frederic (International Symposium on Distributed Computing and Applications to Business, Engineering & Science (Online), 2019)
On modern parallel architectures, the cost of synchronization among processors can often dominate the cost of floating-point computation. Several modifications of the existing methods have been proposed in order to keep the communication cost as low as possible. This paper aims at providing a brief overview of recent advances in parallel iterative methods for solving large-scale problems. We refer the reader to the related references for more details on the derivation, implementation, performance, and analysis of these techniques.